2012
DOI: 10.1094/pdis-12-11-1030
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fusarium mangiferae Causing Mango Malformation in China

Abstract: Verticillium wilt caused by the fungus Verticillium dahliae is found worldwide and attacks a wide range of plants. In the summer of 2001, a wilt disease of Amygdalus communis (sweet almond) cultivated in the Xinjiang municipality in China was first observed. The characteristic symptoms of typical wilt included wilt of leaves and twigs, and brownish discoloration of vascular tissues. Ultimately, the branches and entire trees wilted and died. To identify the causal agent, both traditional and PCR-based methods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“… 12 Recently, F. mangiferae was found to be associated with mango malformation. 13 Here, we morphologically characterized Fusarium sp from mango cv, Dashehri ( Fig. 1A–D ) and found that features (light purple plus white colony colors, shape and size of microconidia and macroconidia, partitionate hyphae with septa and absence of chlamydospores) were in accord with the reported standard features of species F. mangiferae .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“… 12 Recently, F. mangiferae was found to be associated with mango malformation. 13 Here, we morphologically characterized Fusarium sp from mango cv, Dashehri ( Fig. 1A–D ) and found that features (light purple plus white colony colors, shape and size of microconidia and macroconidia, partitionate hyphae with septa and absence of chlamydospores) were in accord with the reported standard features of species F. mangiferae .…”
Section: Discussionsupporting
confidence: 75%
“…More than one species of Fusarium were reported to be involved in the disease 12 . Recently, F. mangiferae was found to be associated with mango malformation 13 . Here, we morphologically characterized Fusarium sp from mango cv, Dashehri ( Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Isolate 26 morphologically resembled F. subglutinans and its comparison in the database showed 99.44% similarity with F. subglutinans, F. sterilihyphosum and F. proliferatum. These two species have already been associated with mango malformation disease around the world according to several studies (Steenkamp et al, 2000;Britz et al, 2002;Zhan et al, 2012;Freeman et al, 2014b) This result is probably due to the fact that the genus Fusarium is a genus that is evolutionarily recent and therefore unstable, hence the importance of the number of species and the variations between species on the same plant and from one plant to another in this genus.…”
mentioning
confidence: 99%